Factors Associated with Re-Admission and Mortality Rate in Low Birth Weight and Very Low Birth Weight Infant - Esmaeili, Maryam; Jashni Motlagh, Alireza; Rahimzadeh, Mitra (International Journal of Psychosocial Rehabilitation, 2020)
Molecular evaluation of thrombophilia panel is one of the practical evaluations in recurrent miscarriage. Clotting and disruption in the uterine placental circulatory system result in miscarriage, intrauterine growth retardation, and preeclampsia. In the Iranian population, it is possible to identify new genetic disorders due to the high rate of kinship marriages and different gene storage. The present study was conducted with the aim of investigating the new mutations in the thrombophilia panel related to recurrent miscarriage. This is a case-control study. The research population consisted of the patients with recurrent miscarriage referred to Kamali Hospital in Karaj. A total of 100 women with recurrent miscarriage (at least 2 miscarriages) and 100 women with at least one successful pregnancy (more than 2 miscarriages) were selected through the convenience sampling method. DNA amplification was performed by PCR. Mutation analysis was performed using Chromes software, and then it was analyzed by SPSS software. In the case group, 10 patients (10%) with the PAI-1 homozygous gene (G/4G4) and, in the control group, 2 patients (2%) with the PAI-1 homozygous gene (G/4G4) were identified, and this difference was statistically significant. Moreover, 20 patients (20%) in the case group and 3 patients (3%) in the control group were positive in terms of MTHFR gene polymorphism, with the difference between the two groups being statistically significant. The results of this study revealed that the presence of the homozygous PAI-1 gene and the MTHFR polymorphism gene increases the risk of recurrent miscarriage. Thus, thrombophilia panel screening is recommended in patients with recurrent miscarriage.